2019
DOI: 10.1016/j.actpsy.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Being observed caused physiological stress leading to poorer face recognition

Abstract: Being observed when completing physical and mental tasks alters how successful people are at completing them. This has been explained in terms of evaluation apprehension, drive theory, and due to the effects of stress caused by being observed. In three experiments, we explore how being observed affects participants' ability to recognise faces as it relates to the aforementioned theorieseasier face recognition tasks should be completed with more success under observation relative to harder tasks. In Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Critically, in a further experiment the same authors showed that the inversion effect was reestablished once that the subjects were provided with humanizing information as regards individuals diagnosed with autism. Hills et al (2019) showed the inversion effect was completely eliminated when the subjects believed they were being observed by the experimenter during the study. The authors suggested that social observation can cause the subjects to become somewhat anxious leading to reduced performance (especially for the upright faces) in a relatively difficult task (recognition of unfamiliar faces).…”
Section: Discussionmentioning
confidence: 96%
“…Critically, in a further experiment the same authors showed that the inversion effect was reestablished once that the subjects were provided with humanizing information as regards individuals diagnosed with autism. Hills et al (2019) showed the inversion effect was completely eliminated when the subjects believed they were being observed by the experimenter during the study. The authors suggested that social observation can cause the subjects to become somewhat anxious leading to reduced performance (especially for the upright faces) in a relatively difficult task (recognition of unfamiliar faces).…”
Section: Discussionmentioning
confidence: 96%
“…In support of this possibility, an early study reported that participants in a moderate arousal condition had higher face recognition ability than those in the high arousal condition [46]. More recently, Hills et al (2019) examined how being observed affects face recognition and found that being observed during learning, but not during the test phase, impaired recognition accuracy using an old/new recognition memory and eyewitness identification paradigms [47]. Although being observed was associated with increased physiological arousal as indexed by galvanic skin response and heart rate, these authors found that this heightened arousal did not explain the detriments in face recognition [47].…”
Section: Individual Differences In Face Recognition and Personality Amentioning
confidence: 99%
“…More recently, Hills et al (2019) examined how being observed affects face recognition and found that being observed during learning, but not during the test phase, impaired recognition accuracy using an old/new recognition memory and eyewitness identification paradigms [47]. Although being observed was associated with increased physiological arousal as indexed by galvanic skin response and heart rate, these authors found that this heightened arousal did not explain the detriments in face recognition [47]. Nevertheless, face recognition has been found to negatively associate with generalized anxiety [44,[48][49][50][51]; but for an inconsistent finding see [52] as well as social anxiety more specifically [53].…”
Section: Individual Differences In Face Recognition and Personality Amentioning
confidence: 99%
See 1 more Smart Citation
“…Hills et al, ( 2019 ) demonstrated that simply being observed was enough to induce stress, and to reduce the ability of the one being observed to perform the task in question. The participating teachers of this study applied this same logic to the CLASS (Pianta et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%